Комишувате – половецьке курганне святилище у Північному Приазов’ї (Серія: Історія. Політологія, 2025)
У статті опубліковано матеріали середньовічних кочівників, здобуті під час досліджень маріупольськими археологами курганної групи біля с. Комишувате у Північному Приазов’ї на півдні Донецької області України у 1989 та 2021 рр. Розглядаються деякі особливості матеріальної і духовної культури середньовічного населення приазовських степів та їх поховальної обрядовості. Проаналізовано поховальний обряд та інвентар поховання 1 кургану 2, що дозволило датувати його ХIII–XIV ст. Розглядаються ритуально-поминальні дії, що здійснювалися на курганах могильника середньовічними кочівниками. Знахідка металевого казана в кургані 1 з певною вірогідністю теж пов’язується із кочівницьким похованням та датується ХIII–XIV ст. Культовий комплекс з кургану 3 також пов’язаний із кочівниками середньовіччя та семантично близький до половецьких святилищ. Яма із залишками дерев’яного виробу, ймовірно, у спрощеному вигляді відображає половецьку традицію влаштовувати у курганах святилища-ями з похованими в них дерев’яними статуями, що є проявом завершального акту поминального обряду. Висловлено припущення, що поховання з кургану 2, кам’яні конструкції, простежені в курганах, а також культовий комплекс з кургану 3 мають безпосередній зв’язок, що дозволяє припустити використання середньовічними кочівниками курганів групи як єдине святилище. Про це додатково свідчать сліди поминальних дій – наявні кістки тварин, уламки кераміки та металевий казан. Всі ці факти є проявами половецьких поминальних обрядів та культу предків, які добре вписуються в рамки світоглядних та ритуальних традицій середньовічних і сучасних тюркських народів. Публікація матеріалів половецького святилища ХIII–XIV ст. біля с. Комишувате збагачує фонд джерел для вивчення матеріальної та духовної культури середньовічних кочівників приазовських степів. The article presents the materials of medieval nomads obtained during the research by Mariupol archaeologists of the mound group near the village of Komyshuvate in the North Azov Area in the south of Donetsk region of Ukraine in 1989 and 2021. Some peculiarities of the material and spiritual culture of the medieval population of the Azov steppes and their funeral rites are considered. The medieval nomads performed ritual and memorial actions on all the burial mounds. The practice of using stone in the construction of burial mounds in the steppe of Eastern Europe was inherited by the nomads and appeared in the Cumans period. An analysis of the burial rites and equipment of burial 1, barrow 2, allows us to date it to the 13th–14th centuries. In addition, all the burial mounds bear traces of ritual and memorial activities associated with medieval nomads. The find of metal cauldron in barrow 1 is also connected with nomadic burial with some probability and is dated 13th–14th centuries. Similar finds, probably, were connected with kurgan sanctuaries. The cauldrons were not only part of the funerary accompaniment of the deceased, but were also used as a necessary object during ritual and cult activities. The cult complex from barrow 3 is also connected with the nomads of the Middle Ages and is semantically close to the Cumans sanctuaries. The pit with a wooden plank vertically embedded in the centre probably in a simplified form reflects the Cumans tradition to arrange sanctuary pits with wooden or stone statues in barrows. This is a manifestation of the final act of the funeral rite. The tradition of making and using wooden statues in mound sanctuaries is characteristic of the Cuman people of the Lower Don steppes. Thus, the stelae studied in the mound near the village of Komyshuvate can be recognised as the westernmost manifestation of this tradition in the North-Eastern Azov region. It is suggested that the burial from barrow 2, the stone structures traced in the mounds, and the cult complex from barrow 3 are directly related. This suggests that medieval nomads used the mounds of the group as a common sanctuary. This is further evidenced by the traces of funeral actions - animal bones, fragments of pottery and a metal cauldron. All of these facts are manifestations of Cumans funeral rites and ancestor worship that fit well within the worldview and ritual traditions of medieval and modern Turkic peoples. The publication of the materials of the 13th–14th centuries Cuman sanctuary Komyshuvate enriches the fund of sources for the study material and spiritual culture of medieval nomads of the Azov steppes.